Eastern African environmental variation and its role in the evolution and cultural change of Homo over the last 1 million years. Issue 157 (August 2021) - Lupien, Rachel L.; Russell, James M.; Subramanian, Avinash; Kinyanjui, Rahab; Beverly, Emily J.; Uno, Kevin T.; de Menocal, Peter; Dommain, René; Potts, Richard
Abstract: Characterizing eastern African environmental variability on orbital timescales is crucial to evaluating the hominin evolutionary response to past climate changes. However, there is a dearth of high-resolution, well-dated records of ecosystem dynamics from eastern Africa that cover long time intervals. In the last 1 Myr, there were significant anatomical and cultural developments in Homo, including the origin of Homo sapiens . There were also major changes in global climatic boundary conditions that may have affected eastern African environments, yet potential linkages remain poorly understood. We developed carbon isotopic records from plant waxes (δ 13 Cwax ) and bulk organic matter (δ 13 COM ) from a well-dated sediment core spanning the last ∼1 Myr extracted from the Koora Basin, located south of the Olorgesailie Basin, in the southern Kenya rift. Our record characterizes the climatic and environmental context for evolutionary events and technological advances recorded in the adjacent Olorgesailie Basin, such as the transition from Acheulean to Middle Stone Age tools by 320 ka. A significant shift toward more C4 -dominated ecosystems and arid conditions occurred near the end of the mid-Pleistocene Transition, which indicates a link between equatorial eastern African and high-latitude northern hemisphere climate. Environmental variability increases throughout the mid- to late-Pleistocene, superimposed by precession-paced packets of variability modulated by eccentricity. An interval of particularly high-amplitude climate and environmental variability occurred from ∼275 ka to ∼180 ka, synchronous with evidence for the first H. sapiens fossils in eastern Africa. These results support the 'variability selection hypothesis' that increased environmental variability selected for adaptable traits, behaviors, and technology in our hominin ancestors. Highlights: We present δ 13 C records from leaf waxes and organic matter from the Koora Basin. C4 ecosystems expanded and landscape variability increased since 1 Ma. Environmental variability was influenced by both regional and global climate factors. Resource instability is linked with change in morphology, behavior, and technology.